Ion size effects in a primitive level model of the diffuse double layer - Fawcett, W.R.; Smagala, T.G. (Condensed Matter Physics, 2004)
An analytical expression is developed for the potential drop across the diffuse layer φ^d in terms of a cubic polynomial in the corresponding estimate in the Gouy-Chapman approximation ϕ^dGC . The coefficients of this polynomial are defined in terms of the hard sphere volume fraction η and the MSA dimensionless reciprocal distance parameter Γ . The resulting expression is shown to describe the Monte-Carlo estimates of φ^d obtained in a primitive level simulation of diffuse layer properties Отримано аналітичний вираз для зниження потенціалу через дифузійний шар φ^d у термінах кубічного поліному в рамках наближення Гуї-Чепмена ϕ^d GC. Коефіцієнти поліному є визначені в термінах об’ємної густини твердих сфер η і безрозмірного параметра оберненої відстані Γ (середньосферичне наближення). Показано, що остаточний вираз описує оцінки для φ^d у примітивній моделі дифузійного шару, отримані методом Монте-Карло.